Front Cover: Single‐Particle Entanglement (Adv. Quantum Technol. 10/2020). Issue 10 (5th October 2020) - Azzini, Stefano; Mazzucchi, Sonia; Moretti, Valter; Pastorello, Davide; Pavesi, Lorenzo
Abstract : The cover shows the input stage of a setup to produce single‐particle entangled states of photons where the momentum and polarization degrees of freedom are entangled (see the formula). A classical light source formed by a green light‐emitting diode is used. The data in the plot show the violation of the Bell inequality by the single‐particle entangled states. Pictorially a Schrödinger cat is testing the photon beam (image author Bianca Moretti). For further details on single‐particle entanglement see the Review by Lorenzo Pavesi and co‐workers, article number 2000014 .